PENGARUH ANALISIS JABATAN DAN ANALISIS PEKERJAAN TERHADAP KINERJA GURU SMP/MTS KECAMATAN LAMPIHONG KABUPATEN BALANGAN - Jamil Rifani (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2019)
This study aims to determine the partial effect of job analysis and job analysis on the performance of SMP / MTs teachers in Lampihong District, Balangan Regency. The study sample numbered 85 people with a Porpusive Sampling technique ie the sample determined by researchers outside the informant was <25% of all SMP / MTs teachers in Lampihong Subdistrict, Balangan Regency. The results of this study are (1) there is a significant influence between job analysis on the performance of SMP / MTs teachers in Lampihong Subdistrict Balangan Regency (t-count> t-table value = 3,223> 1,890); there is a significant influence between job analysis on the performance of SMP / MTs teachers in Lampihong Subdistrict, Balangan Regency (t-count> t-table value = 3,269> 1,890); (3) job analysis and job analysis simultaneously affect the performance of teachers in the SMP / MTs of Lampihong Sub-district of Balangan Regency (f-count> f-table value = 18.098> 4.95); (4) job analysis has a dominant influence on teacher performance compared to job analysis (tcount job analysis = 3,269, tcount job analysis = 3,223).